2015
DOI: 10.7150/jca.12266
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 37 Expression Inhibits STAT3 to Suppress the Proliferation and Invasion of Human Cervical Cancer Cells

Abstract: Objectives: The most recently discovered cytokine interleukin 37 (IL-37) received growing attention. Its function on tumor is largely unknown. Here, we investigated the biological function of IL-37 on cervical cancer (CC).Materials and methods: HPV+ Hela cells and HPV- C33A cells were used. RT-qPCR was performed to detect the transcription of IL-37, STAT3, TNF-αand IL-1β. Western blotting was used for protein detection. CCK-8 assay and transwell assay were employed for cell proliferation and invasion detection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 14 publications
2
58
1
Order By: Relevance
“…IL‐37 has been identified as a natural suppressor of innate inflammatory and immune responses 8, 12. Recent studies have indicated that IL‐37 plays a protective role in tumor progression in mouse fibrosarcoma,9 human lung cancer,14, 42 hepatocellular carcinoma,13 breast cancer,43 cervical cancer,44 and renal cell carcinoma 45. Zhang et al15 found that IL‐37 inhibits colon cancer progression via β‐catenin suppression and that a lack of IL‐37 is associated with poor survival.…”
Section: Discussionmentioning
confidence: 99%
“…IL‐37 has been identified as a natural suppressor of innate inflammatory and immune responses 8, 12. Recent studies have indicated that IL‐37 plays a protective role in tumor progression in mouse fibrosarcoma,9 human lung cancer,14, 42 hepatocellular carcinoma,13 breast cancer,43 cervical cancer,44 and renal cell carcinoma 45. Zhang et al15 found that IL‐37 inhibits colon cancer progression via β‐catenin suppression and that a lack of IL‐37 is associated with poor survival.…”
Section: Discussionmentioning
confidence: 99%
“…After transfection with siSTAT3, CC cell proliferation and invasion inhibited by IL-37 was significantly reversed. STAT3 overexpression restored the CC cell growth and invasion, and increased the transcription of TNF-α and IL-1β (12). IL-37 expression is upregulated in breast carcinoma tissues, which indicates that this cytokine may have a role in tumor progression (9,81).…”
Section: Chronic Inflammatory and Autoimmune Disordersmentioning
confidence: 99%
“…Wang et al offered evidence that IL-37 inhibits the proliferation and invasion of cervical cancer (CC) cells via the signal transducer and activator of transcription 3 (STAT3) signaling pathway (12). IL-37 upregulated STAT3 expression at the gene and protein levels and reduced STAT3 phosphorylation (12). After transfection with siSTAT3, CC cell proliferation and invasion inhibited by IL-37 was significantly reversed.…”
Section: Chronic Inflammatory and Autoimmune Disordersmentioning
confidence: 99%
See 2 more Smart Citations